Highlighting Earnings Management from Islam Perspective - Rediyanto Putra; Inneke Putri Widyani (Journal of Accounting and Investment, 2019)
This study aims to assess the behaviour of earnings management from an Islamic perspective. The form of this research is descriptive qualitative research using Islamic paradigm to make ethical judgments of earnings management actions. The analytical method used in this study is divided into two, namely descriptive and content analysis. This study concludes that basically the existing earnings management in conventional accounting is not in accordance with Islamic values. Earnings management is an act of dhazalim, contrary to the value of honesty (siddiq), contrary to itsar value, and contrary to kosher (halal thayyiban). This study also concluded that managers can create good performance with expected profit pattern based on professionalism value in accordance with Islamic shariah (akhlakul karimah) in order to be in accordance with Islamic sharia principles.